Design and implementation of a community-based mother-to-mother peer support programme for the follow-up of low birthweight infants in rural western Kenya - Wright, Jemma L.; Achieng, Florence; Tindi, Linda; Patil, Manasi; Boga, Mwanamvua; Kimani, Mary; Barsosio, Hellen C.; Juma, Dan; Kiige, Laura; Manu, Alexander; Kariuki, Simon; Mathai, Matthews; et al. (Frontiers in Pediatrics, 2023)
Background: Globally, low birthweight (LBW) infants (< 2,500g) have the highest risk of mortality during the first year of life. Those who survive often have adverse health outcomes. Post-discharge outcomes of LBW infants in impoverished communities in Africa are largely unknown. This paper describes the design and implementation of a mother-to-mother peer training and mentoring programme for the follow-up of LBW infants in rural Kenya. Methods: Key informant interviews were conducted with 10 mothers of neonates (infants<28 days) from two rural communities in western Kenya. These data informed the identification of key characteristics required for mother-to-mother peer supporters (peer mothers) following up LBW infants post discharge. Forty potential peer mothers were invited to attend a 5-day training programme that focused on three main themes: supportive care using appropriate communication, identification of severe illness, and recommended care strategies for LBW infants. Sixteen peer mothers were mentored to conduct seven community follow-up visits to each mother-LBW infant pair with fifteen completing all the visits over a 6-month period. A mixed methods approach was used to evaluate the implementation of the programme. Quantitative data of peer mother socio-demographic characteristics, recruitment, and retention was collected. Two post-training focus group discussions were conducted with the peer mothers to explore their experiences of the programme. Descriptive statistics were generated from the quantitative data and the qualitative data was analysed using a thematic framework. Results: The median age of the peer mothers was 26 years (range 21-43). From March-August 2019, each peer mother conducted a median of 28 visits (range 7-77) with fourteen (88%) completing all their assigned follow-up visits. Post training, our interviews suggest that peer mothers felt empowered to promote appropriate infant feeding practices. They gave multiple examples of improved health seeking behaviours as a result of the peer mother training programme. Conclusion: Our peer mother training programme equipped peer mothers with the knowledge and skills for the post-discharge follow-up of LBW infants in this rural community in Kenya. Community-based interventions for LBW infants, delivered by appropriately trained peer mothers, have the potential to address the current gaps in post-discharge care for these infants.